Study of cranial ultrasound its correlation with perinatal risk factors and its outcome in preterm neonates admitted to Neonatal intensive care unit - Dr. Utkarsha Kinikar; Dr. Sara Dhanawade (Pediatric Review: International Journal of Pediatric Research, 2018)
Aims and Objectives: To determine the frequency of cranial ultrasound abnormalities in preterm neonates in the first week of life. To evaluate the association between cranial ultrasound findings and perinatal risk factors in regard to the immediate clinical outcome.Materials and Methods: This Retrospective study was done in NICU in a tertiary hospital. Records of all preterm neonates (<37weeks) admitted to NICU who underwent neuro-sonography between Jan2016 – Jan2017 were included.Results: Out of 100 preterms, 53% had normal CUS findings while 47% had abnormal finding. Abnormal CUS was significantly associated with gestational age <32weeks (p<0.001) and birth weight <1.5kg (p=0.006).Among the abnormal CUS findings intraventricular hemorrhage was the most common (40.42%) followed by periventricular hyper-echogenicity (21.27%), cystic periventricular leukomalacia (8.51%), parenchymal bleed (8.51%), cysts (8.51%), cerebral edema (6.38%), ventriculomegaly (4.25%) and thalamic injury (2.12%). Neonatal comorbidities associated with abnormal cranial ultrasound were RDS (25.53%), neonatal sepsis (21.27%), birth asphyxia (17.02%), neonatal seizures (8.51%), NEC (6.38%) and others (21.27%). There was significant association between abnormal cranial ultrasound and RDS (p=0.014) and birth asphyxia (p=0.008). Mortality was 36.1% and all had abnormal cranial USG. Intraventricular hemorrhage (76.4%) was the most common cause of death followed by parenchymal bleed (11.7%).Conclusion: There was significant association between abnormal CUS and gestational age and birth weight. Most common abnormality was IVH and it carried the highest mortality. RDS and birth asphyxia had significant association with abnormal ultrasound. Early neurosonography could help in prognosticating immediate outcome and early intervention.